Dakwah Aisyiyah melalui kader Tuberkulosis (Tb) care di Kabupaten Sinjai - Hasmiati, Hasmiati; Rita, Rita; Amiruddin, Amiruddin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2021)
Islamic da'wah is carried out in all sectors, including health. Likewise, Tuberculosis (TB) Care Aisyiyah in Sinjai Regency. The purpose of the study was to determine the form of Aisyiyah preaching through TB Care cadres. This type of research, qualitative, data collection using the method of observation, interviews and documentation. Data analysis applied in this study started from data collection, data reduction, data presentation and drawing conclusions. The results showed that Aisyiyah preaching through TB Care cadres started from mentoring. Assistance of TB Care cadres is carried out periodically, the first visit is called sampling and becomes a discussion partner with patients, and patients' families starting from information on treatment, healing and health (starting from monitoring taking medication for a period of six months to the recovery stage). Furthermore, the form of da'wah carried out by TB Care cadres in broadcasting da'wah through three forms, namely da'wah by oral bill, da'wah bil hal and da'wah bil qalam. The implication of this research is that the delivery of da'wah for TB Care cadres should be optimized by providing knowledge related to da'wah for TB Care cadres.***Dakwah Islam dilakukan di semua sektor, termasuk kesehatan. Begitu juga yang dilakukan oleh Tuberculosis (TB) Care Aisyiyah di Kabupaten Sinjai. Tujuan penelitian untuk mengetahui bentuk dakwah Aisyiyah melalui kader TB Care. Jenis penelitian, kualitatif, pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Analisis data yang diterapkan dalam penelitian ini mulai dari pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dakwah Aisyiyah melalui kader TB Care dimulai dari pendampingan. Pendampingan kader TB Care dilakukan secara berkala, kunjungan pertama disebut dengan pengambilan sampel serta menjadi mitra diskusi terhadap pasien, dan keluarga pasien mulai dari Informasi pengobatan, kesembuhan dan kesehatan (mulai dari pengawasan minum obat selama kurung waktu enam bulan sampai pada tahap kesembuhan). Selanjutnya bentuk dakwah yang dilakukan oleh kader TB Care dalam menyiarkan dakwah melalui tiga bentuk, yakni dakwah secara bil lisan, dakwah bil hal dan dakwah bil qalam. Implikasi penelitian ini bahwa Â penyampaian dakwah kader TB Care hendaknya dioptimalkan dengan memberikan pengetahuan terkait dakwah terhadap kader TB Care.